E-government Governance through SID from a Good governance Perspective (Study of Sugihwaras Village Government): Tata Kelola E-government melalui SID Dalam Perspektif Good governance (Studi Pemerintah Desa Sugihwaras) - Rodiyah, Isnaini; Mursyidah, Lailul; Rustianingsih, Eni (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2025)
The Village Information Sistem is an effort by the central government to improve the information sistem at the village level. The purpose of this research is to analyze and describe concrete problems related to how the Implementation of E-goverment through the Village Information Sistem in the Perspective of Good governance. This research uses descriptive qualitative research methods. The descriptive qualitative method was used to collect as much information as possible about the Village Information Sistem. Data collection methods included observation, interviews, and documentation. The results of this study indicate that in the transparency indicator, there is still a sub menu that is not up to date regarding the use of the realization of funds from the allocated budget and important data related to village development is not available or the page is not found